Analisis Proses Politik Pembahasan dan Penetapan Anggaran Pendapatan dan Belanja Daerah (APBD) Provinsi Riau Tahun Anggaran 2016 - Rury Febrina; Isril (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2016)
The process of preparing a work programs of regional goverments is an integral part of the state financial system which assosiated with establishment of APBN and APBD. This studies will analyse the political processes during the discussion and establishment of Riau Province APBD in 2016. In general, there are 3 stages of discussion and establisment of Riau Province APBD in 2016 namely a discussion of KUA PPAS, framing a RANPERDA APBD, and establisment of APBD. However a discrepancy in the implementation schedue to the prevailing regulation lead to a non optimal discussion RKA SKPD, RAPBD and RANPERDA APBD where the entire process is done on December 2016. The political process on discussion and establishment of APBD on DPRD of Riau Province is observed on discussion of KUA PPAS that involving TAPD and Budgetary Board. The general overview of DPRD fraction to the RAPBD will be answered by local goverment and then DPRD plenary session wil be held to made a decision that supported by all DPRD members toward RAPBD to APBD, the plenary session will be concluded with the final opinion of The Mayor.